Groups of prime power order - Berkovich, Yakov; Janko, Zvonimir (Berlin ; Walter de Gruyter, 2016)
Offers a comprehensive and elementary treatment of finite p-group theory. In this book, topics covered include theory of linear algebras and Lie algebras. It contains many dozens of original exercises (with difficult exercises being solved) and a list of about 900 research problems and themes.
Includes bibliographical references and indexes.
Keywords: Finite groups; Group theory